Predictive Association between Perceived Social Support and Infertility-Related Stress in Married Couples in Pakistan: Infertility-Related Stress in Married Couples - Abdul Ghafoor, Amna; Mushtaq, Rabia (Pakistan BioMedical Journal, 2024)
Infertility is indeed a global issue and has a profound impact on married couples, affecting various aspects of their relationship, emotional well-being, and quality of life. The WHO estimates that 10-15% of couples globally experience infertility, with rates varying across regions. Objective: To examine the predictive association between perceived social support (PSS) and infertility-related stress among married couples experiencing infertility. Methods: For this research, 50 married couples selected through purposive sampling from the Gynecology and Obstetrics departments of several hospitals and infertility clinics in Karachi, Pakistan with the age ranged between 20-40 years (X̄=32.3; SD= 3.12). Brief interviews of the participants were conducted, and Urdu versions of the Multidimensional Scale of Perceived Social Support and Infertility-Related Stress Scale were administered. Data was analyzed through SPSS (V-25.0) using descriptive statistics, and regression analysis. Results: The findings showed a significant predictive association between perceived social support and infertility stress (R2=.540, β=-.73, P< 0.00). Conclusions: This highlights a significant predictive association between the stress associated with infertility and the level of perceived social support, which significantly impacts individuals coping with fertility difficulties. These findings have implications for offering compassionate and efficient care, devising customized interventions and support programs for couples encountering fertility issues, and offering guidance to hospitals